Shyness and Learning Adjustment in Senior High School Students: Mediating Roles of Goal Orientation and Academic Help Seeking - Chen, Yingmin; Li, Liang; Wang, Xiaoyi; Li, Yingli; Gao, Fengqiang (Frontiers in Psychology, 2018)
This study examined the relationship between shyness and learning adjustment and the mediating roles of goal orientation (i.e., mastery-approach goals, mastery-avoid goals, performance-approach goals, and performance-avoid goals) and academic help seeking (i.e., instrumental help seeking from teacher, instrumental help seeking from classmate, executive help seeking, and avoidance of help seeking). The study sample comprised 677 senior high school students (371 girls; 220 in grade one, 230 in grade two) from two public secondary schools in China. The students completed anonymous questionnaires regarding shyness, goal orientation, academic help seeking, and learning adjustment. Structural equation model was used to examine the hypotheses. Analysis results indicated that shyness directly predicted the students’ learning adjustment. Shyness indirectly predicted learning adjustment through the multi mediating roles of goal orientation and academic help seeking. These findings demonstrate that goal orientation and academic help seeking are critical factors in shy adolescents’ learning adjustment.